The Pengaruh Penyelenggaraan MICE dan Jumlah Kamar Terjual Terhadap Pendapatan Makanan dan Minuman di The Trans Resort Bali - Erick Erlangga; Irene Hanna H Sihombing; Ni Made Suastini (JURNAL BISNIS HOSPITALITI, 2022)
This study aims to determine how much influence the MICE implementation and the number of rooms sold have on food and beverage income at The Trans Resort Bali. The data used in this study are income reports from 2017 – 2021. The research method consists of classical assumption test consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, multiple regression analysis, t test, F test and coefficient determination. Based on the results of the analysis conducted, it shows that the implementation of MICE and the number of rooms sold have a significant effect on food and beverage income with the results of the multiple regression equation Y = 5.016 + 0.269 X1 + 1.109 X2. These results indicate that the implementation of MICE and the number of rooms sold partially have a positive effect on food and beverage income. The implementation of MICE and the number of rooms sold simultaneously have a significant effect on food and beverage income. The amount of contribution contributed by the MICE organization and the number of rooms sold to food and beverage income is 93% while the remaining 7% is influenced by variables that are not used in this study.